Exploring contextual factors for management and prevention of running-related injuries: runners and experts’ perspectives - Caroline Bolling; Manuela Besomi; Sonia Roa-Alcaino; Ángela Lombardi; Rocío Vélez-Rivera; Jaime Leppe Zamora (BMJ Open Sport & Exercise Medicine)
Running is one of the most accessible and popular physical activities worldwide; however, injuries are the main barrier to sustaining running practice. While quantitative studies have explored prevalence and risk factors, a critical gap exists in understanding subjective experiences, perceptions and contextual influences on injury management and prevention. This qualitative study aimed to explore the perspectives of runners and experts regarding injury perception, management and prevention, as well as the contextual influence of these processes. Using a secondary data analysis approach, this study drew from qualitative semistructured interviews with Chilean runners (n=15) and running experts (n=6). Thematic analysis, guided by an interpretivist approach, uncovered intrinsic factors (identity, motivation, stress and self-learning) and extrinsic factors (environment, information sources, marketing, peer advice, professional guidance, racing, stereotype and clothing) that shaped runners’ behaviours. Less experienced runners associated injury risk with asphalt surfaces, faced challenges in discerning online information reliability and found motivation in peer advice. Experts emphasised the multifactorial nature of running-related injuries, including previous injuries and training-related factors. Both groups acknowledged a global tendency among runners to resist rest when discomfort arose. This research contributed to a nuanced understanding of injury perception, management and prevention, bridging scientific knowledge with individual experiences. Clinicians may use this information to enhance the therapy alliance and set realistic expectations about the runner’s rehabilitation process.